Kekayaan Ragam Hias dalam Wayang Kulit Purwa Gagrak Surakarta (sebagai Inspirasi Desain Komunikasi Visual) - Lintang Widyokusumo (Bina Nusantara University, 2010)
Shadow puppet (wayang) is a fine culture heritage; the sublimity of philosophy and its beauty of inlay and decoration already get its world acknowledgement. Wayang is a shadow of out own life, from which we get picture of life in the world and after world. Eventhough its presence now is defeated by modern entertainment, its elegance done by the beauty of graphic sculpture brings its own inspiration to sculpturers and designers to make it as a foundation in design masterpieces toward Indonesian culture, especially Javanese culture.